PEMBUATAN MI KERING DENGAN PENAMBAHAN TEPUNG TULANG CEKER AYAM - Novidahlia, Noli (JURNAL PERTANIAN, 2011)
Noodle is one food type with begins to be liked as food alternative for most people because itâs more practical, easy to process and itâs quicker to serve than rice. Noodle products especially dry noodle commonly doesnât have a balanced nutritional composition, that the proportion of carbohydrate relatively higher than another nutritional content. One of alternative way to increase nutritional content in the dry noodle is adding chicken metatarsal meal on making dry noodle process. By increasing chicken metatarsal meal, it was expected solve nutrition problems on dry noodle product, especially protein and mineral content. This research consisted of four stages. First stage was performed the making of chicken metatarsal meal process and chemical analysis to chicken metatarsal meal result. Second stage was performed to the making of dry noodle with adding 5%, 10%, 15% and 20% chicken metatarsal meal. Third stage was performed to determine chicken metatarsal meal concentration degree which was liked by panelist on the color, texture, aroma and taste of noodle, also to determine the nutritional content from dry noodle formula which are liked by panelist. Fourth stage was performed to determine difference of panelist acceptance to the dry noodle without and with consists of chicken metatarsal meal. The test for third and fourth stage was using organoleptic hedonic method with 7 scales and which were comprise of 30 semi trained panelists. The result of research, showed that dry noodle formula which was liked by panelists are dry noodle with 5% chicken metatarsal meal formula with the average values from panelists to color parameter are 5.23 (fairly like), texture parameter were 4.88 (fairly like), aroma parameter were 4.07 (common) and taste parameter were 4.77 (fairly like). The result of t-test, showed that the adding chicken metatarsal meal on making dry noodle is difference of color, texture, aroma, and taste parameters. The panelists rated that dry noodle without chicken metatarsal meal was better like than dry noodle with chicken metatarsal meal. The chemical analysis was performed to selected formula from organoleptic test result. From the chemical analysis result has been known that nutritional composition of dry noodle with 5% chicken metatarsal meal consist of water 9.76%, ash 4.51%, fat 6.10%, protein 14.90%, carbohydrate 64.73% and calcium 2.23%.